Designed to win - Yoshihara, Hiroaki (McGraw-Hill, 2006)
The most successful business organizations are those that combine stability, speed and maneuverability. These companies are uniquely equipped to navigate the complexities of global supply chains, an array of often baffling cultural differences, complex international regulations, geopolitical uncertainty, and the vagaries of the capital markets. But these companies are only as good as the officers who command them-and the most successful leaders are those best able to manage and optimize their global risk. They possess a singular skill set that includes, among other things, a talent for international diplomacy